2023
DOI: 10.1007/s11154-023-09790-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase angle in localized bioimpedance measurements to assess and monitor muscle injury

Abstract: Localized bioimpedance (L-BIA) measurements are an innovative method to non-invasively identify structural derangement of soft tissues, principally muscles, and fluid accumulation in response to traumatic injury. This review provides unique L-BIA data demonstrating significant relative differences between injured and contralateral non-injured regions of interest (ROI) associated with soft tissue injury. One key finding is the specific and sensitive role of reactance (Xc), measured at 50 kHz with a phase-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Ultimately, based on this finding, we can assume that Xc/Hs is indirectly related to the cell content in a water solution, which supports its translational value as a biomarker of cell integrity or quality. 10 On the other hand, Xc/Hp enables a differential description of cells and ICW and, perhaps, a quantification of body cell mass. 13,16,18 As mentioned before, the standard commercial BIA devices provide R and Xc assuming a series resistor and capacitor array and thus the mixture of resistors and capacitors at 50 kHz.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultimately, based on this finding, we can assume that Xc/Hs is indirectly related to the cell content in a water solution, which supports its translational value as a biomarker of cell integrity or quality. 10 On the other hand, Xc/Hp enables a differential description of cells and ICW and, perhaps, a quantification of body cell mass. 13,16,18 As mentioned before, the standard commercial BIA devices provide R and Xc assuming a series resistor and capacitor array and thus the mixture of resistors and capacitors at 50 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the human body, water and cells exist in parallel, thus the equation to transform from series to parallel equivalence partially accounts for this physiological model of cells and water because of the real RC electrical circuit in the human body. 10,15 Thus, the parallel transformation of series BI measurements is a plausible hypothesis for the complex expression of cells (membranes) and fluid distributions. Congruently, at least two studies 16,19 reported the direct correlation between total body potassium from wholebody 40K counting and CAP and Xc parallel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traumatic muscle injury is endemic in sport. Nescolarde et al [14] describe the innovative method of localized BIA (L-BIA) and its application to identify the severity of injury and track healing until the injury has healed adequately to return to play. They carefully elucidate the technical criteria for valid L-BIA measurements including placement of electrodes on injured and contralateral non-injured region of interest to reliably determine pathology-induced perturbations in L-BIA measurements.…”
mentioning
confidence: 99%